Commuting to and from work and factors associated among industrial workers from Southern Brazil - Silva, Shana Ginar da; Del Duca, Giovâni Firpo; Silva, Kelly Samara da; Oliveira, Elusa Santina Antunes de; Nahas, Markus Vinícius (Revista de Saúde Pública, 2012)
Cross-sectional study that aimed to estimate the prevalence of forms of commuting to and from work and to identify factors associated among industrial workers in the State of Rio Grande do Sul, southern Brazil. A total of 2,265 workers completed a questionnaire on the forms of commuting to and from work (walking/biking, bus or car/motorcycle). Multinomial logistic regression was used to estimate the association between the outcome and sociodemographic, occupational and behavioral variables. The main form of commuting to and from work was by bus (45.7%). Workers with higher socioeconomic condition were more likely to engage in passive commuting.